Is depression associated with pathways to care and diagnosis delay in people with tuberculosis in Ethiopia?. (2019) - Ambaw, F.; Mayston, R.; Hanlon, C.; Alem, A.
Abstract : Background: Co-morbid depression is common in people with tuberculosis (TB). Symptoms of depression (low energy, impaired concentration, decreased motivation and hopelessness) may affect help-seeking; however, this impact has not been studied so far. The objectives of this study were to assess the impact of co-morbid depression on diagnostic delay, pathways to care, and to identify if it mediates other factors associated with diagnostic delay. Methods: We analyzed cross-sectional data collected from 592 adults with newly diagnosed TB. We assessed probable depression using Patient Health Questionnaire, nine items (PHQ-9) at a cut-off 10. Data on diagnosis delay, pathways to TB care, socio-demographic variables, stigma, types of TB, substance use, co-morbid chronic illnesses, and perception about TB were assessed using a structured questionnaire. Generalized structural equation modelling was used to analyze the data. Results: A total of 313 (52.9%) participants had probable depression. Pathway to TB care was direct for 512 (86.5%) of the participants and indirect for 80 (13.5%) of them. The median diagnosis delay was 12.0 weeks. Depression did not have a statistically significant association with pathways to TB care ( β = −0.45; 95% CI−1.85 to 0.96) or diagnostic delay [adjusted odds ratio (AOR) = 0.90; 0.77–1.06]. Indirect pathway to TB care was positively associated with diagnosis delay (AOR = 2.72; 95% CI 1.25–5.91). Conclusions: People with TB who had co-morbid probable depression visited the modern health care as directly as and as soon as those without co-morbid depression. How socio-demographic factors influence pathways to care and diagnosis delay require qualitative exploration.